Effect Observation of Comprehensive Pulmonary Rehabilitation Therapy combined with Acupoint Application in Elderly Patients with COPD - Houmei TANG; Xiaohong GU; Juan DENG (康复学报)
Objective:To evaluate the effect of comprehensive pulmonary rehabilitation therapy combined with acupoint application therapy in elderly patients with chronic obstructive pulmonary disease (COPD).Methods:A total of 120 elderly patients with COPD were randomly divided into control group and observation group, with 60 cases in each group. The control group was treated with comprehensive pulmonary rehabilitation therapy, the observation group was treated with comprehensive pulmonary rehabilitation therapy combined with acupoint application therapy on the basis of control group.After treatment for three years, the immune functions of natural killer cells (NK), interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α) in two groups were evaluated; the clinical symptoms of cough, expectoration and dyspnea were evaluated by visual simulation score (VAS);the quality of life was evaluated by BODE index;and observe the adverse reactions.Results:Compared with treatment before, NK, FEV1percentage of predicted value, 6-minute walking distance (6MWD) in the two groups increased significantly, IFN-γ, TNF-α, cough, sputum and dyspnea scores reduced significantly, and the improvement degree of the observation group was significantly better than that of the control group, with statistically significant difference (P<0.05).Conclusion:Comprehensive pulmonary rehabilitation therapy combined with acupoint application can improve the immune function of elderly patients with COPD, alleviate clinical symptoms, and improve exercise endurance and quality of life..